Preaching John 8:31-36: reforming contexts then and now - Lewis, Karoline M. (Word & world, 2016)
The Gospel reading for Reformation Sunday is always John 8:31–36, yet preaching on this passage tends to overlook the critical contexts in which this pericope is located. Preaching John 8:31–36 on Reformation now will demand a careful analysis of the role of the passage in the Fourth Gospel, both as a means by which to respect its literary integrity as well as invitation to how it might shape a new hermeneutic for a new day.